Methadone dose in heroin‐dependent patients: role of clinical factors, comedications, genetic polymorphisms and enzyme activity. (June 2015) - Mouly, Stéphane; Bloch, Vanessa; Peoc'h, Katell; Houze, Pascal; Labat, Laurence; Ksouda, Kamilia; Simoneau, Guy; Declèves, Xavier; Bergmann, Jean Francois; Scherrmann, Jean‐Michel; Laplanche, Jean‐Louis; Lepine, Jean‐Pierre; et al.
<x xml:space="preserve">Abstract</x> Aims Methadone is characterized by wide intersubject variability regarding the dose needed to obtain full therapeutic response. We assessed the influence of sociodemographic, ethnic, clinical, metabolic and genotypic variables on methadone maintenance dose requirement in opioid‐dependent responder patients. Methods Eighty‐one stable patients (60 men and 21 women, 43.7 ± 8.1 years old, 63.1 ± 50.9 mg day−1 methadone), divided into quartiles with respect to the median daily dose, were enrolled and underwent clinical examination, treatment history and determination of liver/intestinal cytochrome P450 (CYP) 3A4 activity measured by the midazolam test, R, S‐methadone trough concentration and clinically significant polymorphisms of the OPRM1, DRD2, COMT, ABCB1, CYP2B6, CYP3A5, CYP2C19 and CYP2D6 genes. Results Methadone maintenance dose was correlated to the highest dose ever used (r2 = 0.57, P < 0.0001). Fractioned methadone intake (odds ratio 4.87, 95% confidence interval 1.27–18.6, P = 0.02), bodyweight (odds ratio 1.57, 95% confidence interval 1.01–2.44, P = 0.04), history of cocaine dependence (80 vs. 44 mg day−1 in never‐addict patients, P = 0.005) and ethnicity (Asian > Caucasian > African, P = 0.04) were independently associated with high‐dose methadone in multiple regression analysis. A modest correlation was observed between liver/intestinal CYP3A4 activity and methadone dose at steady state (Spearman rank correlation coefficient [rs] = 0.21, P = 0.06) but not with highest dose ever used (rs = 0.15, P = 0.18) or dose‐normalized R, S‐methadone trough concentrations (rs = −0.05, P = 0.64). Concomitant CYP3A4 inhibitors only affected the relationship between methadone dose and R, S‐methadone trough concentration. None of the genetic polymorphisms explored was predictive of the methadone maintenance dose. Conclusions Methadone maintenance dose was predicted by sociodemographic and clinical variables rather than genetic polymorphisms or liver/intestinal CYP3A4 activity in stable patients.